Partisipasi dan Agensi: Perempuan Muda selama Advokasi UU TPKS - Andi Misbahul Pratiwi (Jurnal Perempuan, 2023)
Since a decade ago, the women’s movement in Indonesia has consolidated its power to advocate for policies aimed at eliminating sexual violence through legislative advocacy and public campaigns. These efforts were a response to the increasing cases of sexual violence and the absence of a legal framework to address the issue. In the process of policy advocacy, young women have played a crucial role by participating in formal and informal political processes, although their participation has often been overlooked and unrecognized. This research examines the dynamics of young women’s activism in various forms at the national level in the advocacy process for Sexual Violence Criminal Law (UU Tindak Pidana Kekerasan Seksual/UU TPKS). This research aims to demonstrate the role and forms of activism among young women in advocating policies related to sexual violence. The study utilizes a qualitative methodology through in-depth interviews with eight young women activists involved in the advocacy, lobbying, and campaigning to pass the bill. The research finds that young women face various barriers and challenges, but simultaneously demonstrate their agency in the policy advocacy process.